Literature Review: The Technology Problems on YouTube as a Learning Media for Math Subjects at Elementary School - Putra, Randi Eka; Trisnawati, Winda (PPSDP International Journal of Education, 2023)
Technological developments have an important role in increasing the progress of the use of learning media in teaching practice, this is inseparable from its problems. The researcher aims to analyze the use of learning media, especially YouTube technology. Researchers discuss the use of YouTube video learning media, but no one has explained explicitly about the use of YouTube-based technology in learning Mathematics in Elementary Schools. This study used the literature review method by collecting articles from several EBSCO and Scopus databases with a time span of 2019-2023, as many as 6 articles were analyzed according to the keyword YouTube-based technology in learning mathematics. The results of the study were then analyzed and in accordance with the research as many as 6 articles. The results of the research show that the use of YouTube-based technology as a medium for learning is found at various levels of education that the researchers reviewed.